Charles E. Curran, Diverse Voices in Modern US Moral Theology, Georgetown University Press, Washington, DC 2018, ss. XIII+264, ISBN 978-16-2616-633-2 - Nowosad, Sławomir (Teologia i Moralność, 2022)
Recenzja: Charles E. Curran, Diverse Voices in Modern US Moral Theology, Georgetown University Press, Washington, DC 2018, ss. XIII+264, ISBN 978-16-2616-633-2.